Pemberdayaan Literasi Digital untuk Guru dan Murid di Pondok Pesantren As’ad Kota Jambi - Nasir Nasir; Asmawati Asmawati; Netti Zurnelli (Lembaga Pengembangan Kinerja Dosen, 2025)
The digital literacy program implemented at the As'ad Islamic Boarding School in Jambi City aims to improve the digital skills of teachers and students through the use of information and communication technology, specifically Google Workspace and artificial intelligence (AI). The program consists of four training sessions that include an introduction to Google Docs, Google Sheets, Google Classroom, and the use of ChatGPT as a learning tool. This training is designed to introduce digital technology to participants who previously had limitations in using technology-based applications. Evaluation was conducted through interviews and direct observations that showed a significant improvement in the digital skills of participants, although challenges related to limited devices and internet connectivity remained major obstacles. The positive impact of this program is expected to serve as a model for the development of digital literacy in other remote areas and support the transformation of technology-based education in Indonesia.